Pendampingan Penulisan dan Publikasi Artikel Ilmiah Bereputasi Internasional untuk Peneliti dan Akademisi Universitas Nahdlatul Ulama Indonesia - Vika Nurul Mufidah; Fatkhu Yasikh; Juri Ardiantoro; Muhammad Nurul Huda; Unu Putra Herlambang (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2022)
The objectives of this service are, 1) to improve the understanding and competence of lecturers in writing and publishing scientific articles of international repute; 2) provide assistance to lecturers in writing scientific articles; 3) improve lecturers' understanding regarding how to publish scientific articles in international reputable journals. As a result of this activity, lecturers are able to understand and start writing scientific articles in accordance with the standards of international reputable journals and are able to select and sort out journals of international repute that are detected as 'discontinued'. This can be proven by their enthusiasm in participating in workshop activities and the mentoring process.